1996
DOI: 10.1007/bf02231680
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in leprosy sera

Abstract: Our objective was to assess the prevalence of autoantibodies in patients with leprosy. Forty-one cases of lepromatous leprosy were studied. For the detection of autoantibodies we used the Elisa technique using the following purified antigens in an Elisa assay: dsDNA, ssDNA, histone, mitochondria, RNA, RNP, SS-A, SS-B, Sm, Scl-70, Anca C, Anca P and the cardiolipin complex. As a "cut off" point we used values shown on previous studies to differentiate normal from elevated values. Antibodies to SS-B, mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“… 25 Autoantibodies are widely reported in leprosy, especially in patients with the LL form. 26–30 This might explain the presence of β 2 ‐GP1‐dependent anti‐PL and, consequently, the positive RR.…”
Section: Discussionmentioning
confidence: 98%
“… 25 Autoantibodies are widely reported in leprosy, especially in patients with the LL form. 26–30 This might explain the presence of β 2 ‐GP1‐dependent anti‐PL and, consequently, the positive RR.…”
Section: Discussionmentioning
confidence: 98%
“…MB leprosy is often associated with an autoimmune phenomenon with various autoantibodies, such as anti-neutrophil cytoplasmic antibodies (ANCA), A-ANCA, anti-mitochondrial antibodies, and anti-phospholipid antibodies, found in the sera of patients (Freire et al, 1998, Garcia-De La Torre, 1993, Guedes Barbosa et al, 1996, Park et al, 1992). Hence, it has been suggested that autoantibodies directed against components of the ovary might be a cause of ovarian failure.…”
Section: Effect Of Leprosy On Menstrual Cycle and Fertility Statusmentioning
confidence: 99%
“…Another possible mechanism might be that of molecular mimicry due to the cross reactivity between the infecting antigen and self antigens. 4,24 Ribeiro et al. recently reported the relationship between vitamin D deficiency and development of ANA, suggesting that vitamin D might be a pathogenic link for the emergence of auto-immunity in patients with leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…4 A variety of auto-antibodies can be detected in leprosy patients such as antibodies to SS-B, anti-mitochondrial antibodies, antiphospholipid antibodies and anti-dsDNA. 24…”
Section: Discussionmentioning
confidence: 99%